2018
DOI: 10.20944/preprints201812.0170.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanocellulose in Biotechnology and Medicine: Focus on Skin Tissue Engineering and Wound Healing

Abstract: Nanocellulose is cellulose in the form of nanostructures, i.e. features not exceeding 100 nm at least in one dimension. These nanostructures include nanofibrils, e.g. in bacterial cellulose; nanofibers, e.g. in electrospun matrices; nanowhiskers and nanocrystals. These structures can be further assembled into bigger 2D and 3D nano-, micro- and macro-structures, such as nanoplatelets, membranes, films, microparticles and porous macroscopic matrices. There are four main sources of nanocellulose: bacteria (Gluona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 197 publications
(248 reference statements)
0
1
0
Order By: Relevance
“…After promoting cellular characteristics, they demonstrated that crosslinking hydroxypropyl methylcellulose with chitosan can endow the recovery process with structural strength and shape. The use of HPMC as a composite hydrogel in scaffold engineering was also investigated by Bacakova et al [84]. Likewise, HPMC is widely used to make composite hydrogels using different polysaccharides (Figure 4B).…”
Section: Hydroxypropyl Methyl Cellulose (Hpmc)mentioning
confidence: 89%
“…After promoting cellular characteristics, they demonstrated that crosslinking hydroxypropyl methylcellulose with chitosan can endow the recovery process with structural strength and shape. The use of HPMC as a composite hydrogel in scaffold engineering was also investigated by Bacakova et al [84]. Likewise, HPMC is widely used to make composite hydrogels using different polysaccharides (Figure 4B).…”
Section: Hydroxypropyl Methyl Cellulose (Hpmc)mentioning
confidence: 89%